Bimetal–organic-frameworks-derived yolk–shell-structured porous Co2P/ZnO@PC/CNTs hybrids for highly sensitive non-enzymatic detection of superoxide anion released from living cells. Issue 84 (3rd October 2016) - Wang, Min-Qiang; Ye, Cui; Bao, Shu-Juan; Zhang, Yan; Xu, Mao-Wen; Li, Zhe
Abstract : Bimetal-organic framework derived yolk–shell–structured porous Co2 P/ZnO@PC/CNTs were used as highly active electrocatalysts for electrochemical sensing of superoxide anions. Abstract : We report a general approach for the synthesis of yolk–shell-structured porous dicobalt phosphide/zinc oxide@porous carbon polyhedral/carbon nanotube hybrids (Co2 P/ZnO@PC/CNTs) derived from bimetal–organic frameworks, and explore their potential utilization in the electrochemical sensing of superoxide anions. Beyond our expectation, the trace level of O2 ˙ − released from living cells has also been successfully captured by our designed sensor. The presented strategy for the controlled design and synthesis of bimetal–organic frameworks-derived functional nanomaterials offers prospects of developing highly active electrocatalysts in non-enzyme sensors.